2019
DOI: 10.3390/ijerph16173125
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Combined Intervention on Psychological and Physical Capacities of Frail Older Adults: A Cluster Randomized Controlled Trial

Abstract: Background: Older adults experience physical and psychological declines affecting independency. Adapted and structured combined interventions composed of cognitive stimulation and physical exercise contribute to comorbidities’ reduction. Methods: Multicenter single-blinded two-arm cluster randomized controlled trial conducted to assess effectiveness of a combined intervention (CI), composed of a cognitive stimulation program (CSP) and a physical exercise program (PEP), on psychological and physical capacities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…As with the previous variables investigated here, there are a few studies that have been carried out on active older adults without physical deterioration or pathology. Previous works confirmed an improvement in performance of daily activities by the older adults studied, but their results were not separated by intensity [13].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…As with the previous variables investigated here, there are a few studies that have been carried out on active older adults without physical deterioration or pathology. Previous works confirmed an improvement in performance of daily activities by the older adults studied, but their results were not separated by intensity [13].…”
Section: Discussionmentioning
confidence: 61%
“…In addition to this, many authors have shown that physical activity improves the functional abilities of older adults [9][10][11] as well as their quality of life [12]. In a combined intervention study of physical activity and cognitive stimulation carried out in a sample of 50 older adults where 44 were women [13], an improvement in the functional abilities and activities of daily living were observed. Moreover, a recent review on this subject [14], concluded that combined strength and aerobic training causes improvements in the functional capacity and quality of life of older adults.…”
Section: Introductionmentioning
confidence: 93%
“…BMI was calculated as weight/height 2 , and BMI ≥ 30.0 kg/m 2 was recognized as obesity. 21 Lean mass (kilogram), a proxy measure for muscle mass, was obtained from whole-body dual-energy X-ray absorptiometry (Lunar Prodigy-Pro, Madison, WI, USA), which provided lean mass measures for appendicular lean mass (ALM), equivalent to the sum of lean mass for the arms and legs. ALM was expressed relative to height as ALM/height 2 (kilograms per square metre) or BMI as ALM/BMI (square metre).…”
Section: Methodsmentioning
confidence: 99%
“…Weight and height were measured to the nearest ±0.1 kg and ±0.001, m and body mass index (BMI) was calculated as weight/height 2 (kilograms per square metre). BMI was calculated as weight/height 2 , and BMI ≥ 30.0 kg/m 2 was recognized as obesity 21 . Lean mass (kilogram), a proxy measure for muscle mass, was obtained from whole‐body dual‐energy X‐ray absorptiometry (Lunar Prodigy‐Pro, Madison, WI, USA), which provided lean mass measures for appendicular lean mass (ALM), equivalent to the sum of lean mass for the arms and legs.…”
Section: Methodsmentioning
confidence: 99%
“…Although several systematic reviews of randomized clinical trials (RCTs) on the management of frailty have been published, [18][19][20][21][22][23][24][25][26][27] those reviews emphasized interventions associated with physical activity and exercise whilst nutritional interventions were assessed briefly and in a secondary manner, if at all. Hence, although nutrition is considered an important intervention for the management of frailty, the actual effectiveness of interventions addressing nutrition in frail older people remains unclear.…”
Section: Introductionmentioning
confidence: 99%